RAMESES publication standards: meta-narrative reviews. - Wong, G; Greenhalgh, P; Westhorp, G; Buckingham, J; Pawson, R (BioMed Central, 2013)
BACKGROUND: Meta-narrative review is one of an emerging menu of new approaches to qualitative and mixed-method systematic review. A meta-narrative review seeks to illuminate a heterogeneous topic area by highlighting the contrasting and complementary ways in which researchers have studied the same or a similar topic. No previous publication standards exist for the reporting of meta-narrative reviews. This publication standard was developed as part of the RAMESES (Realist And MEta-narrative Evidence Syntheses: Evolving Standards) project. The project's aim is to produce preliminary publication standards for meta-narrative reviews. METHODS: We (a) collated and summarized existing literature on the principles of good practice in meta-narrative reviews; (b) considered the extent to which these principles had been followed by published reviews, thereby identifying how rigor may be lost and how existing methods could be improved; (c) used a three-round online Delphi method with an interdisciplinary panel of national and international experts in evidence synthesis, meta-narrative reviews, policy and/or publishing to produce and iteratively refine a draft set of methodological steps and publication standards; (d) provided real-time support to ongoing meta-narrative reviews and the open-access RAMESES online discussion list so as to capture problems and questions as they arose; and (e) synthesized expert input, evidence review and real-time problem analysis into a definitive set of standards. RESULTS: We identified nine published meta-narrative reviews, provided real-time support to four ongoing reviews and captured questions raised in the RAMESES discussion list. Through analysis and discussion within the project team, we summarized the published literature, and common questions and challenges into briefing materials for the Delphi panel, comprising 33 members. Within three rounds this panel had reached consensus on 20 key publication standards, with an overall response rate of 90%. CONCLUSION: This project used multiple sources to draw together evidence and expertise in meta-narrative reviews. For each item we have included an explanation for why it is important and guidance on how it might be reported. Meta-narrative review is a relatively new method for evidence synthesis and as experience and methodological developments occur, we anticipate that these standards will evolve to reflect further theoretical and methodological developments. We hope that these standards will act as a resource that will contribute to improving the reporting of meta-narrative reviews.